2020
DOI: 10.1109/access.2020.3016913
|View full text |Cite
|
Sign up to set email alerts
|

Effective Influence Spreading in Temporal Networks With Sequential Seeding

Abstract: The spread of influence in networks is a topic of great importance in many application areas. For instance, one would like to maximise the coverage, limiting the budget for marketing campaign initialisation and use the potential of social influence. To tackle this and similar challenges, more than a decade ago, researchers started to investigate the influence maximisation problem. The challenge is to find the best set of initially activated seed nodes in order to maximise the influence spread in networks. In t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…As we have mentioned, temporal inhomogeneities can strongly affect, i.e., promoting or slowing down, the spreading dynamics on the temporal networks. [10][11][12][13][14][15] To specify the information-spreading dynamics on the temporal networks constructed by the Vicsek model, the simple susceptibleinfected (SI) model is employed. An active particle can only have two states, either susceptible or infected.…”
Section: Information Spreading Dynamics On the Temporal Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have mentioned, temporal inhomogeneities can strongly affect, i.e., promoting or slowing down, the spreading dynamics on the temporal networks. [10][11][12][13][14][15] To specify the information-spreading dynamics on the temporal networks constructed by the Vicsek model, the simple susceptibleinfected (SI) model is employed. An active particle can only have two states, either susceptible or infected.…”
Section: Information Spreading Dynamics On the Temporal Networkmentioning
confidence: 99%
“…9 Besides, it can also suppress or promote the spreading dynamics on the temporal networks. [10][11][12][13][14][15] Vazquez et al 16 analyzed the spreading dynamics of a temporal contact network. They found that the interevent time distribution of the edges exhibits a heavy tail, which indicates the system's heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…As we have mentioned, that the temporal inhomogeneities can strongly affect, i.e., promoting or slowing down, the spreading dynamics on the temporal networks [10][11][12][13][14][15].…”
Section: Information Spreading Dynamcis On the Temporal Networkmentioning
confidence: 99%
“…When the bursty nature of a signal is identified, it can produce aging effects, resulting in the breaking of the time translation invariance of the degree distribution, in the corresponding time-integrated network [9]. Besides, it can also suppress or promote the spreading dynamics on the temporal networks [10][11][12][13][14][15]. Vazquz et al [16] analyzed the spreading dynamics on the temporal contact network, of which the interevent time distribution of the edges exhibits a heavy-tail, i.e., it is a temporally inhomogeneous bursty contact process.…”
Section: Introductionmentioning
confidence: 99%
“…By recording the process of spreading the influence/information in a community, the temporal network provides a comprehensive description of time-dependent network structures such as social networks, traffic networks, communication networks, logistics networks, etc. Such comprehensiveness paves the way to many studies on the timedependency of networks [1][2] [3].…”
Section: Introductionmentioning
confidence: 99%